2015
DOI: 10.1039/c5an00122f
|View full text |Cite
|
Sign up to set email alerts
|

The real-time in vivo electrochemical measurement of nitric oxide and carbon monoxide release upon direct epidural electrical stimulation of the rat neocortex

Abstract: This study reports real-time, in vivo functional measurement of nitric oxide (NO) and carbon monoxide (CO), two gaseous mediators in controlling cerebral blood flow. A dual electrochemical NO/CO microsensor enables us to probe the complex relationship between NO and CO in regulating cerebrovascular tone. Utilizing this dual sensor, we monitor in vivo change of NO and CO simultaneously during direct epidural electrical stimulation of a living rat brain cortex. Both NO and CO respond quickly to meet physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
(46 reference statements)
0
26
0
Order By: Relevance
“…In addition, the decrease in HO-2 expression, which produces CO, may contribute to the reduced functional hemodynamic responses in the stress group, although the role of CO in stress has not been reported. Recent evidence from an in vivo microsensor study demonstrates that CO has a tight relationship with increased metabolic demands and cerebral blood flow (Park et al, 2015 ). In this study, the endogenous CO release nicely reflects the robust hemodynamic response, which is induced by epidural electrical stimulation in the rat somatosensory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the decrease in HO-2 expression, which produces CO, may contribute to the reduced functional hemodynamic responses in the stress group, although the role of CO in stress has not been reported. Recent evidence from an in vivo microsensor study demonstrates that CO has a tight relationship with increased metabolic demands and cerebral blood flow (Park et al, 2015 ). In this study, the endogenous CO release nicely reflects the robust hemodynamic response, which is induced by epidural electrical stimulation in the rat somatosensory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The NO sensors demonstrated negligible responses (<1%) from most of the interfering species including ascorbic acid, serotonin, DOPAC, dopamine, l -gluthathione, hydrogen peroxide, 5-HIAA, homovanillic acid, nitrite and uric acid. Further selectivity studies were undertaken against more recent identified interferents including the electroactive gasotransmitters CO and H 2 S. Concentrations representative of their physiological levels were chosen [23,24]. A comparable selectivity over H 2 S (<1%, 1.6 ± 0.1 pA·µM −1 , n = 4) and a slightly higher contribution from CO (ca.…”
Section: Methodsmentioning
confidence: 99%
“…These fixed and modifiable risk factors give rise to the injury mediators amyloid b, inflammation, reactive oxygen and nitrogen species (RONS), and suppression of endothelial nitric oxide synthase (eNOS) which, in turn, damage macro-and microvascular components of the cerebral circulation. The resultant impairment of cerebral blood supply causes neurodegeneration which culminates in neurocognitive impairment peptides [25][26][27] associated with altered tissue PO 2 . 28 However, atherosclerotic disease in the cerebral supply arteries limits the vascular reserve that is required for autoregulation of cerebral blood flow and exposes the otherwise healthy, active brain to the potential damage of sustained hypoxia and ischemia.…”
Section: Cerebrovascular Function and Admentioning
confidence: 99%